Identification and expression analysis of sex biased miRNAs in chinese hook snout carp Opsariichthys bidens - Tang, Rongkang; Xu, Cong; Zhu, Yefei; Yan, Jinpeng; Yao, Ziliang; Zhou, Wenzong; Gui, Lang; Li, Mingyou (Frontiers in Genetics, 2022)
As an economically important fish, Opsariichthys bidens has obvious sexual dimorphism and strong reproductive capacity, but no epigenetics study can well explain its phenotypic variations. In recent years, many microRNAs involved in the regulation of reproductive development have been explored. In this study, the small RNA libraries of O. bidens on the testis and ovary were constructed and sequenced. A total of 295 known miRNAs were obtained and 100 novel miRNAs were predicted. By comparing testis and ovary libraries, 115 differentially expressed (DE) miRNAs were selected, of which 53 were up-regulated and 62 were down-regulated. A total of 64 GO items (padj < 0.01) and 206 KEGG pathways (padj < 0.01) were enriched in the target gene of miRNA. After that, the expression levels of nine DE miRNAs, including let-7a, miR-146b, miR-18c, miR-202-5p, miR-135c, miR-9-5p, miR-34c-3p, miR-460-5p and miR-338 were verified by qRT-PCR. Furthermore, bidirectional prediction of DE miRNAs and sex-related genes was carried out and the targeting correlation between miR-9-5p and nanos1 was verified by Dual-Luciferase reporter assay. Our findings identified the differentially expressed miRNA and paved the way to new possibilities for the follow-up study on the mechanism of miRNA-mRNA interaction in the gonads of O. bidens.